Convento di Santa Clara de Asis, L’Avana - Cuba / Convento de Santa Clara de Asís, La Habana - Cuba (Firenze University Press, 2025)
The monograph is part of the INNOVA CUBA project, a multi-year partnership between ARCS and the Office of the Historian of the City of Havana (OHCH). The aim is to strengthen the preservation, enhancement, and dissemination of Cuban cultural heritage through collaboration between institutions and local communities. A key objective has been to promote the use of technological and methodological innovations in the conservation of built cultural heritage. Various entities were involved, including Assorestauro, Fundación Tecnalia, Academy of Fine Arts in Warsaw, University of Florence, AITR, Arci Toscana, and DiaCon srl, already a UNIFI Spin-off. The monograph gathers contributions from project participants who describe the case study and offer proposals for the restoration and repurposing of the Convent into a Training Center for Heritage Management and Conservation for Cuba and the Caribbean.